Analysis of the impact of technologies and methods of hologram transmission on the parameters and effects of transmission - Mazur, Krzysztof; Mazur, Damian (Journal of Computer Sciences Institute, 2019)
The aim of the article is to compare and analyze the impact of technologies and data transfer techniques in term of displaying the image using a holographic pyramid. When assessing the usability of the solution, the following parameters will be taken into account: time of image transfer, use of physical parameters of the machine and parameters of the Java Virtual Machine.